Optimization of a rowing seat using human modeling and 3D printing technology - Boin, M.; Goebel, G.; Hofmann, H.; Hummel, S. (Hochschule Ulm, 2018)
Content: 1. Motivation 2. Simulation Method and Model Setup 3. Simulation Results 4. Imprints and 3D Printing 5. Final Results 6. Future Tasks and Open Questions